Continuities of the Political Space in Chilean Theater: Dramaturgy and Human Rights in Isidora Aguirre and Guillermo Calderón (2024)
The goal of this work is to analyze the political continuity surrounding two Chilean dramaturgical texts: Retablo de Yumbel by Isidora Aguirre, and Villa by Guillermo Calderón. The former was written and staged during the civil-military dictatorship, while the latter belongs to the post-dictatorial period. The reflection is developed through a comparative analysis, drawing upon theories that explore the concept of politics. Specifically, the relationship between human rights violations committed under the dictatorshipand the theater is examined. The article concludes that references to the history are made using a variety of stylistic allusive techniques, including those of self and metacognitive reflection. In both works, the word serves as both an aesthetic and dramatic device as well as an emotive one. Through this exploration, the art delves into its political possibilities from an ethical perspective.